THE STUDENTS’ ABILITY IN USING CONJUNCTIONS (A DESCRIPTIVE QUANTITATIVE STUDY OF THE SIXTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM BENGKULU UNIVERSITY) - Rahma Syafitri; Arasuli .; Barnabas Sembiring (Journal of English Education and Teaching, 2017)
The purpose of this research was to describe the ability of the students in 6th semester of English study program in using English conjunctions. The design of this research used descriptive quantitative study. The population of this research was 78 students in English study program Bengkulu University and the samples were 65 students. In collecting the data, the researcher used multiple choices conjunctions test. Based on the finding of the research, the ability of the students in using coordinate conjunctions was in enough category with the mean scores 61.  The ability of the students in using correlative conjunction was good with the mean scores 79. The ability of the students in using relative conjunction was good with the mean score 78. The ability of the students in using subordinate conjunction was good with mean score 78, the same as the ability in using relative conjunction. According to the result in every type of conjunctions, the researcher concluded that the ability of the students in using conjunctions was in enough category with the mean score 74.